PATI RESISTEN SAGU HASIL PROSES HIDROLISIS ASAM DAN AUTOCLAVING-COOLING - Feri Kusnandar; Heru Pitria Hastuti; Elvira Syamsir (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2015)
The aim of this study was to produce resistant starch (RS) from a combination of acid hydrolysis and autoclaving-cooling processes of sago starch. This study compared two methods of starch modification to produce RS, i.e. (1) acid hydrolysis treatment followed by autoclaving-cooling cycles (AH-AC), and (2) autoclaving-cooling cycles followed by acid hydrolysis treatment (AC-AH). The acid hydrolysis used 1 and 2% HCl while autoclaving-cooling process consisted of three-cycle of autoclaving at 121°C for 30 min followed by cooling at 4°C for 72 hrs. Both AH-AC and AC-AH modification methods decreased starch content, altered amylose and amylopectin ratio, and increased RS contents. Both modification methods also yielded nearly flat pasting profiles at both heating and cooling phases as compared to that of native sago starch. At the same HCl concentration, the AH-AC process yielded a higher RS content than that of AC-AH. Among all treatments, the acid hydrolysis treatment using 1% HCl followed by three cycles of autoclaving-cooling process yielded the highest RS content (74.28%). The crystallinity of RS was also lower than of native sago starch, but its A crystalline type remained the same.